'A harmless but confusing tumour on the anterior maxilla'. (23rd May 2012) - Emmanuel, Roby V; Neelakantan, Shiba; Nair, Preeti P; Thomas, Shaji; Saxena, Vrinda; Yadav, Niranjan S
Abstract : Squamous odontogenic tumour (SOT) is a very rare benign neoplasm probably arising from rests of Malassez. Patients may present with an increase in the volume of the maxilla or mandible, tooth mobility, ulceration of the oral soft tissue, painful symptoms and tooth displacement. Radiographic features of SOT consist of a triangular-shaped radiolucent lesion adjacent to the roots of teeth. Histologically, care should be taken not to misdiagnose this condition as acanthomatous ameloblastoma or well-differentiated squamous cell carcinoma. The authors are presenting a case of a 65-year-old male patient who presented with a painless swelling and diagnosed to be having SOT.